ANALISIS MASALAH GIZI SEBAGAI SALAH SATU FAKTOR RISIKO YANG MEMPENGARUHI KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS MARGADADI KABUPATEN INDRAMAYU PERIODE OKTOBER - DESEMBER 2022 - Muhammad Yusuf Athallah Lubis, (2023)
Indonesia is experiencing nutritional problems which have a very serious impact on the quality of human resources (HR). The purpose of this study was to analyze nutritional problems as a risk factor that can influence the incident of stunting in toddlers, such as knowledge, attitudes and behavior of mothers regarding nutritional intake at the Puskesmas. This research is a quantitative study with a cross-sectional study design, the sample was taken using a consecutive sampling methods from a questionnare. Based on univariate analysis of stunting in toddlers there were 27 respondents (30,3%), high knowledge 62 respondents (69,7%), good attitude 68 respondents (76,4%) and good behavior 72 respondents (80,9%). The results of bivariate analysis showed that there was a relationship between knowledge (p=0,016), attitude (p=0,012), and behavior (p=0,024) with the incidence of stunting in toddlers. The results of multivariate analysis show that attitudes about nutritional intake in mother's have an influence and the most dominant variable affecting the incidence of stunting in toddlers. There is a relationship between knowledge, attitudes, and behavior of mothers regarding nutritional intake with the incidence of stunting and the effect of attitudes regarding poor nutrition has the highest chance of causing stunting in toddlers by 0,280 times.